Fabrication and Characterisation of ZnO Thin Film by Sol–Gel Technique - Benramache Said (Annals of West University of Timisoara: Physics, 2019)
We investigated the structural and optical properties of zinc oxide (ZnO) thin film as the n-type semiconductor. In this work, the sol–gel method used to fabricate ZnO thin film on glass substrate with 0.5 mol/l of zinc acetate dehydrates. The crystals quality of the thin film analyzed by X-ray diffraction and the optical transmittance was carried out by an ultraviolet-visible spectrophotometer. The DRX analyses indicated that ZnO film have polycrystalline nature and hexagonal wurtzite structure with (002) preferential orientation and the measured average crystallite size of ZnO of 207.9 nm. The thin film exhibit average optical transparency about 90 %, in the visible region, found that optical band gap energy was 3.282 eV, the Urbach energy also was calculated from optical transmittance to optimal value is 196.7 meV.